The effects of grass and rainfall pattern on the matric suction of acidic soil slopes - Md Isa, Siti Fazlina (2019)
Among the mechanism that leads to slope failures are that the matric suction starts to decrease when water infiltrates the soil. Although many studies have been carried out to improve stability of slope, most studies often ignore the influence of matric suction induced by vegetation. Grass can be classified into many different types and appearances. For this research, Bermuda grass and Signal grass were used to investigate matric suction due to rainfall by applying hydromulching on sloping ground. Despite numerous efforts in the past to investigate the influence of rainfall infiltration on slope stability, there was limited research on the effect of both rainfall infiltration and evaporation on sloping ground. This study provides an insight on how matric suction changes after applying hydromulching on the sloping ground of acidic soil slopes. A large-scale model (with four slope surfaces) and rainfall simulator were used to measure the matric suction of soil at a depth of 20 cm by a soil moisture sensor. This research investigate the variations in matric suction profiles under a loose and compact soil condition, treated and untreated dolomite, bare plot and a grassed surface in acidic soil slopes response to rainfalls pattern. The field monitoring results showed the ability of both (Signal & Bermuda) grass covers to maintain the matric suction on acidic soil slopes during rainfall. The rate of changes in suction for bare slope surface is much faster as compared to grass-covered slope surface. The finding showed the hydromulching creates grass cover on top of acidic soil slopes and the grass influence the matric suction. The thesis has contributed to some original outcomes. First, how distribution of matric suction changes in sloping ground after apply hydromulching. Second, implementation of an easy and effective matric suction measurement method by using sensors in field work. Last, the results of the study proved that the hydromulching method with additives such as dolomite, fertilisers can be used for this acidic soil.